Magnetostrictive material as well as preparation method and application thereof
Through the mixing of TbDyFe alloy and epoxy resin and the magnetic field orientation pressurization treatment, magnetostrictive materials with high magnetostrictive performance under low magnetic fields were prepared, which solved the problem of insufficient performance under high magnetic fields and high pressure in the prior art, achieved cost-effectiveness improvement and material toughness improvement, and was suitable for pipeline inspection.
Patent Information
- Application Number
- CN202510692010.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-27
- Publication Date
- 2025-08-12
AI Technical Summary
The existing magnetostrictive materials can only show good performance under high magnetic fields and high pressures, and are highly prepared and brittle, making it difficult to meet the online pipeline inspection requirements in conventional environments.
TbDyFe alloy ball milling powder or spherical powder is mixed with epoxy resin, and after magnetic field orientation, pressurization and heating treatment, magnetostrictive materials with high magnetostrictive properties under low magnetic field strength were prepared.
It achieves better magnetostrictive performance and high magnetic field sensitivity under low magnetic field strength, reduces production costs and improves the toughness of the material, and is suitable for pipeline inspection in conventional environments.
Smart Images

Figure CN120464133A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a magnetostrictive material and a preparation method and application thereof. Background Art
[0002] Traditional nondestructive testing generally relies solely on single-point testing, making it difficult to meet the current needs of large-scale online pipeline inspection. Developing an economical, practical, fast, and efficient inspection technology is a pressing need in the pipeline inspection industry. Magnetostrictive materials, which recover their shape in the presence of an applied magnetic field and change their magnetic properties when stressed, offer advantages such as high energy density, fast response, and high reliability. They are important materials (waveguides) for energy and information conversion, meeting the needs of online pipeline inspection.
[0003] Current magnetostrictive waveguide materials include two types: FeCo-based strips (FeCo-based strips). These strips are bonded to pipes for detection. While FeCo-based strips are ductile, they exhibit poor magnetostrictive properties, resulting in limited signal accuracy. Another type is coatings, primarily applied through thermal spraying processes such as flame spraying. While these coatings exhibit improved saturation magnetostriction, the majority of these coatings are applied in atmospheric environments and at high temperatures, requiring a sufficiently stable magnetostrictive material. This limits the selection of materials, and existing magnetostrictive materials exhibit optimal magnetostrictive properties only under high magnetic fields and / or high pressures.
[0004] CN102569638A discloses a method having a layered structure with a high <111> The invention relates to a bonded rare earth giant magnetostrictive material with high resistance and low loss characteristics and a preparation method thereof. The alloy particles used in the magnetostrictive material are composed of Tb x Dy 1-x Fe y(0.4<x≤1,1.9≤y≤1.95). The preparation method comprises: mixing alloy particles with a particle size of 10 to 300 μm, a binder (epoxy resin E44, epoxy resin E51 or epoxy resin 6101), a curing agent (triethylenetetramine, menthane diamine or m-phenylenediamine) and a process control agent (methanol, propanol or n-pentane), and then performing dynamic magnetic field orientation under the induction of a magnetic field of 6000 to 12000 Oe, with a dynamic magnetic field frequency of 0.5 to 10 Hz; finally, curing and molding in a static magnetic field and a water bath of 40 to 60°C, thereby obtaining a layered structure with high <111> A bonded rare earth giant magnetostrictive material with preferential orientation and a large magnetostrictive strain of 1900 ppm. The preparation of this magnetostrictive material requires the addition of a curing agent and process control agents. The introduction of these additives increases production costs and can easily lead to increased brittleness of the magnetostrictive material. During guided wave testing, the magnetostrictive material is prone to cracking or shedding. The preparation method requires orientation in a relatively high magnetic field, resulting in high production costs. This magnetostrictive material only exhibits optimal magnetostrictive properties under high magnetic fields and high pressures, making it unsuitable for use in conventional environments.
[0005] CN102766792A discloses a method for preparing a bonded rare earth iron giant magnetostrictive material. The preparation comprises the following steps: first, Tb or Sm, Dy, and Fe are mixed in proportion and arc-melted under high-purity argon protection to obtain an alloy ingot, followed by homogenization annealing at 700-950°C for 45-50 hours, furnace cooling to room temperature, then crushing and grinding the alloy ingot into a powder with a particle size of 50-180 μm, compacting and performing a secondary stress relief annealing at 300-500°C for 5-8 hours under high-purity argon protection, finally mixing the powder with a binder (epoxy resin HY-914), placing it in a mold for pressurization, and curing it in a magnetic field for 36-48 hours after demolding to obtain a bonded rare earth iron giant magnetostrictive material. The preparation method of this magnetostrictive material requires two annealings and the annealing time is long, which significantly increases the production cost.
[0006] CN111850387A discloses a magnetostrictive composite material for waveguide detection, which includes the following components by weight: 35 to 60 parts of terbium-dysprosium-iron alloy powder, 20 to 30 parts of epoxy resin, a dispersant (any one or more of acetone, n-butanol, xylene and ethyl acetate), a curing agent (amine curing agent), and also includes a rigidity modifier (polyurethane), polydimethylsiloxane and sodium hexametaphosphate. The preparation method of the magnetostrictive composite material comprises the following steps: preparing terbium-dysprosium-iron alloy powder by magnetic levitation melting; uniformly mixing the terbium-dysprosium-iron alloy powder, epoxy resin, dispersant, rigidity modifier, polydimethylsiloxane and sodium hexametaphosphate to form a premix; placing the curing agent and the premix separately and mixing them when using. The preparation of the magnetostrictive material requires the addition of a curing agent, a rigidity modifier, polydimethylsiloxane and sodium hexametaphosphate. The introduction of more additives will increase production costs and easily cause the magnetostrictive material to become more brittle. During guided wave testing, magnetostrictive materials are prone to cracking or falling off. The preparation method uses magnetic levitation smelting to prepare terbium-dysprosium-iron alloy powder, which is too costly. Summary of the Invention
[0007] In view of this, one object of the present invention is to provide a method for preparing a magnetostrictive material. The resulting magnetostrictive material exhibits good magnetostrictive properties at relatively low magnetic field intensities and high magnetic field sensitivity. Another object of the present invention is to provide a magnetostrictive material produced by the above-mentioned preparation method. A further object of the present invention is to provide a use of the above-mentioned magnetostrictive material.
[0008] The present invention adopts the following technical solutions to achieve the above-mentioned purpose.
[0009] In one aspect, the present invention provides a method for preparing a magnetostrictive material, comprising the following steps:
[0010] 1) mixing ball-milled powder or spherical powder of TbDyFe alloy with epoxy resin in a weight ratio of 1:0.2-1 to obtain a mixed powder;
[0011] 2) placing the mixed powder obtained in step 1) in a mold and compacting it, and then orienting the mixed powder in a magnetic field at a magnetic field strength of 350 to 4000 Oe to obtain an oriented mixed material;
[0012] 3) Pressing the oriented mixture obtained in step 2) at 50 to 400 MPa to obtain a pressed sheet;
[0013] 4) heating the pressed sheet obtained in step 3) at 80-150° C., cooling, and demolding to obtain a magnetostrictive material.
[0014] According to the preparation method of the present invention, preferably, the chemical composition of the TbDyFe alloy is Tb a Dyb Fe c , a, b, c represent the number of atoms, a=0.1~0.5, b=0.5~1, c=1~3.
[0015] According to the preparation method of the present invention, preferably, the preparation method of the ball-milled powder of the TbDyFe alloy comprises the following steps:
[0016] a) crushing the TbDyFe alloy to obtain an alloy block; grinding the alloy block for 2 to 10 seconds to obtain a grinding powder;
[0017] b) ball milling the disc milled powder for 10 to 90 minutes at a ball-to-material weight ratio of 1:0.2 to 0.9 to obtain a coarse ball milled powder;
[0018] c) sieving the coarse ball-milled powder to separate powder with a particle size of 65 to 150 μm to obtain ball-milled powder of TbDyFe alloy.
[0019] According to the preparation method of the present invention, preferably, the preparation method of the spherical powder of the TbDyFe alloy comprises the following steps:
[0020] A) melting the TbDyFe alloy at 1500-1800°C to obtain a molten alloy;
[0021] B) Under the conditions of protective gas and atomizing pressure of 2-5 MPa, impacting the alloy liquid into spherical powder to obtain coarse spherical powder;
[0022] C) The coarse spherical powder is sieved to separate powder with a particle size of 65 to 150 μm, thereby obtaining spherical powder of TbDyFe alloy.
[0023] According to the preparation method of the present invention, preferably, in step 2), the time of the magnetic field orientation is 200 to 500 seconds.
[0024] According to the preparation method of the present invention, preferably, in step 3), the pressurization time is 10 to 60 minutes.
[0025] According to the preparation method of the present invention, preferably, in step 4), the heating time is 10 to 60 minutes.
[0026] On the other hand, the present invention also provides a magnetostrictive material prepared by any of the above preparation methods, wherein the magnetostrictive coefficient of the magnetostrictive material is greater than 15 ppm at a magnetic field intensity of 200 Oe and greater than 200 ppm at a magnetic field intensity of 1000 Oe.
[0027] In another aspect, the present invention further provides use of the magnetostrictive material in guided wave detection of metal materials.
[0028] In another aspect, the invention further provides a method for detecting metal materials by guided waves, comprising the following steps:
[0029] 1) mixing ball-milled powder or spherical powder of TbDyFe alloy with epoxy resin in a weight ratio of 1:0.2-1 to obtain a mixed powder;
[0030] 2) Using the metal material to be tested as the base of the mold, covering the upper surface of the metal material to be tested with the mixed powder, assembling the mold, and compacting the mixed powder in the mold. Then, the mixed powder is magnetically oriented at a magnetic field strength of 350 to 4000 Oe to obtain an oriented mixed powder and metal material assembly;
[0031] 3) Pressing the oriented mixed material and the metal material assembly at 50-400 MPa to obtain a pressed sheet and the metal material assembly;
[0032] 4) heating the pressed sheet and the metal material assembly at 80-150° C., cooling, and demolding to obtain a magnetostrictive material and metal material assembly;
[0033] 5) Place the combination of magnetostrictive material and metal material under a magnetic field and perform guided wave detection on the metal material to be tested.
[0034] The magnetostrictive material of the present invention has a magnetostriction coefficient of greater than 15 ppm at a magnetic field strength of 200 Oe and a magnetostriction coefficient of greater than 200 ppm at a magnetic field strength of 1000 Oe. The magnetostrictive material of the present invention exhibits good magnetostrictive properties at lower magnetic field strengths and high magnetic field sensitivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is the magnetostrictive curve of the magnetostrictive material of Example 1.
[0036] Figure 2 This is the magnetostrictive curve of the magnetostrictive material of Example 2.
[0037] Figure 3 : is the magnetostrictive curve of the magnetostrictive material of Comparative Example 1.
[0038] Figure 4 This is the magnetostrictive curve of the magnetostrictive material of Comparative Example 2.
[0039] Figure 5 This is a frequency scanning diagram when the magnetostrictive material of Example 1 is used for guided wave detection.
[0040] Figure 6 This is a waveform signal diagram when the magnetostrictive material of Example 1 is used for waveguide detection. DETAILED DESCRIPTION
[0041] The present invention will be further described below with reference to specific embodiments, but the protection scope of the present invention is not limited thereto.
[0042] The "magnetostriction coefficient" mentioned in the present invention refers to the relative dimensional change (strain) of a magnetostrictive material under the action of an external magnetic field, which is represented by λ and has a unit of ppm.
[0043] <Method for preparing magnetostrictive material>
[0044] The preparation method of the magnetostrictive material of the present invention comprises a material mixing step, a magnetic field orientation step, a pressurizing step, and a heating step, which will be described in detail below.
[0045] Mixing steps
[0046] The ball-milled powder or spherical powder of the TbDyFe alloy is mixed with the epoxy resin in a weight ratio of 1:0.2-1 to obtain a mixed powder.
[0047] According to one embodiment of the present invention, the weight ratio of the ball-milled powder or spherical powder of the TbDyFe alloy to the epoxy resin may be 1:0.2-1, preferably 1:0.3-0.9, and more preferably 1:0.4-0.8.
[0048] According to one embodiment of the present invention, the epoxy resin may be at least one of epoxy resins E20, E44, E12, and E06, preferably at least one of E20, E44, and E12, and more preferably at least one of E20 and E12.
[0049] Limiting the type and amount of epoxy resin to the aforementioned ranges can increase the toughness of the magnetostrictive material, allowing the magnetostrictive material to be fixed to the surface of the metal material to be detected without the need for other additives and preventing it from falling off. This saves costs and is conducive to the magnetostrictive material having better magnetostrictive properties at lower magnetic field intensities, thereby improving the magnetic field sensitivity of the magnetostrictive material.
[0050] According to one embodiment of the present invention, the chemical composition of the TbDyFe alloy may be Tb a Dy b Fe c, a, b, and c represent the number of atoms. The value of a can be 0.1 to 0.5, preferably 0.15 to 0.45, and more preferably 0.2 to 0.4. The value of b can be 0.5 to 1, preferably 0.55 to 0.95, and more preferably 0.6 to 0.9. The value of c can be 1 to 3, preferably 1.2 to 2.8, and more preferably 1.5 to 2.5. A reasonable composition of the TbDyFe alloy can ensure that the powder obtains better magnetic field orientation at a lower magnetic field intensity, saving costs while being more conducive to the prepared magnetostrictive material having better magnetostrictive properties at a lower magnetic field intensity, thereby improving the magnetic field sensitivity of the magnetostrictive material.
[0051] In the present invention, mixing can be achieved using any mixing equipment known in the art, which will not be described in detail herein, for example, a spiral mixer, a V-shaped mixer, a double cone mixer, etc.
[0052] According to one embodiment of the present invention, a method for preparing ball-milled powder of TbDyFe alloy may include the following steps:
[0053] a) crushing the TbDyFe alloy to obtain an alloy block; grinding the alloy block for 2 to 10 seconds to obtain a grinding powder;
[0054] b) ball milling the disc milled powder for 10 to 90 minutes at a ball-to-material weight ratio of 1:0.2 to 0.9 to obtain a coarse ball milled powder;
[0055] c) sieving the coarse ball-milled powder to obtain powder with a particle size of 65 to 150 μm, thereby obtaining ball-milled powder of TbDyFe alloy.
[0056] According to one embodiment of the present invention, in step a), the particle size of the alloy block can be 2 to 8 mm, preferably 2 to 6 mm, and more preferably 3 to 6 mm. Crushing can be achieved using any crushing method or device known in the art, which will not be described in detail here.
[0057] According to one embodiment of the present invention, in step a), the disc grinding speed may be 1000-1500 rpm, preferably 1050-1450, more preferably 1100-1400. The disc grinding time may be 2-10 s, preferably 2-8 s, more preferably 3-8 s.
[0058] In the present invention, the disc grinding can be achieved using any wet disc grinding machine known in the art, which will not be described in detail here. The disc grinding medium can use any liquid medium known in the art, which will not be described in detail here, for example, petroleum ether. The amount of the disc grinding medium used can be 1 to 6 mL per gram of alloy block, preferably 2 to 6 mL per gram of alloy block, and more preferably 2 to 5 mL per gram of alloy block.
[0059] According to one embodiment of the present invention, in step b), the ball-to-material weight ratio during ball milling can be 1:0.2-0.9, preferably 1:0.3-0.9, more preferably 1:0.3-0.8. The ball milling time can be 10-90 min, preferably 15-85 min, more preferably 20-80 min.
[0060] In the present invention, ball milling can be achieved using any wet ball mill known in the art, which will not be described in detail here. The grinding body of the ball mill can be made of any material known in the art, which will not be described in detail here. For example, it can be agate balls, steel balls, zirconium beads or alumina balls. The medium of the ball mill can be any liquid medium known in the art, which will not be described in detail here. For example, it can be petroleum ether. The amount of the medium used in the ball mill can be 5 to 10 mL per gram of alloy block, preferably 6 to 10 mL per gram of alloy block, and more preferably 6 to 9 mL per gram of alloy block.
[0061] According to one embodiment of the present invention, in step c), the particle size of the powder may be 65 to 150 μm, preferably 70 to 140 μm, and more preferably 75 to 130 μm.
[0062] Reasonable ball milling conditions can ensure that the powder is better refined, which is conducive to the magnetostrictive material having better magnetostrictive properties at lower magnetic field intensity and improving the magnetic field sensitivity of the magnetostrictive material.
[0063] According to one embodiment of the present invention, a method for preparing spherical powder of TbDyFe alloy may include the following steps:
[0064] A) melting the TbDyFe alloy at 1500-1800°C to obtain a molten alloy;
[0065] B) impacting the alloy liquid into spherical powder under protective gas and an atomizing pressure of 2 to 5 MPa to obtain a coarse spherical powder; and obtaining a spherical powder of TbDyFe alloy;
[0066] C) The coarse spherical powder is sieved to separate powder with a particle size of 65 to 150 μm, thereby obtaining spherical powder of TbDyFe alloy.
[0067] According to one embodiment of the present invention, in step A), the melting temperature may be 1500-1800° C., preferably 1600-1780° C., more preferably 1650-1750° C. The melting time may be 2-10 min, preferably 3-9 min, more preferably 4-8 min.
[0068] In the present invention, smelting can be achieved using any smelting equipment known in the art, which will not be described in detail here, such as a vacuum smelting furnace, a medium frequency induction smelting furnace, an electric arc furnace, etc.
[0069] The present invention may further include a step of cleaning the TbDyFe alloy prior to smelting. Cleaning can be accomplished using any method or apparatus known in the art, which will not be described in detail herein. For example, the surface oxide scale of the alloy may be removed first, and then the surface of the alloy may be polished clean.
[0070] The protective gas involved in the present invention can be selected from at least one of nitrogen and inert gases, and the inert gases include helium (He), neon (Ne), argon (Ar), krypton (Kr), and xenon (Xe); preferably, the protective gas is at least one of nitrogen, helium, neon, and argon; more preferably, the protective gas is at least one of nitrogen, helium, and argon.
[0071] According to one embodiment of the present invention, in step B), the atomization pressure may be 2-5 MPa, preferably 2.5-4.5 MPa, and more preferably 3-4 MPa.
[0072] In the present invention, step B) can be implemented in any spherical powder atomization equipment known in the art, which will not be described in detail here.
[0073] According to one embodiment of the present invention, in step C), the particle size of the powder may be 65 to 150 μm, preferably 70 to 140 μm, and more preferably 75 to 130 μm.
[0074] Reasonable spherical powder preparation conditions can ensure that the powder is better refined, which is conducive to the magnetostrictive material having better magnetostrictive properties at lower magnetic field intensity and improving the magnetic field sensitivity of the magnetostrictive material.
[0075] The TbDyFe alloy used in the present invention can be a commercial product or prepared by an existing preparation method, which will not be described in detail here. The purity of the TbDyFe alloy of the present invention is at least industrial purity (99.9 wt%).
[0076] Magnetic field orientation step
[0077] The mixed powder is placed in a mold and compacted, and then the mixed powder is oriented in a magnetic field at a magnetic field strength of 350 to 4000 Oe to obtain an oriented mixed material.
[0078] According to one embodiment of the present invention, the magnetic field intensity may be 350 to 4000 Oe, preferably 400 to 3800 Oe, more preferably 450 to 3500 Oe. The magnetic field orientation time may be 200 to 500 s, preferably 220 to 450 s, more preferably 250 to 400 s.
[0079] In the present invention, the mold may be any mold known in the art that can be used for magnetic field orientation, and will not be described in detail here.
[0080] According to one embodiment of the present invention, after compaction, the mixed powder may be in the shape of a cuboid, wherein the length of the cuboid may be 20 to 80 mm, preferably 25 to 75 mm, and more preferably 30 to 70 mm. The width of the cuboid may be 8 to 12 mm, preferably 8 to 11 mm, and more preferably 9 to 11 mm. The thickness of the cuboid may be 1 to 5 mm, preferably 1 to 4 mm, and more preferably 2 to 4 mm.
[0081] Reasonable magnetic field orientation conditions are conducive to the magnetostrictive material having better magnetostrictive properties at lower magnetic field intensity and improving the magnetic field sensitivity of the magnetostrictive material.
[0082] Pressurization step
[0083] The oriented mixture is pressed at 50 to 400 MPa to obtain a pressed sheet.
[0084] According to one embodiment of the present invention, the pressurization pressure may be 50-400 MPa, preferably 30-380 MPa, more preferably 80-350 MPa, and the pressurization time may be 10-60 min, preferably 15-55 min, more preferably 20-50 min.
[0085] In the present invention, pressurization can be achieved in any pressurizing device known in the art, which will not be described in detail herein. For example, it can be a tablet press.
[0086] Reasonable pressurizing conditions are beneficial to improving the density of the oriented mixture, and are more conducive to the magnetostrictive material having better magnetostrictive properties at lower magnetic field intensity, thereby improving the magnetic field sensitivity of the magnetostrictive material.
[0087] Heating steps
[0088] The pressed sheet is heated at 80-150° C., cooled, and demoulded to obtain a magnetostrictive material.
[0089] In one embodiment of the present invention, the heating temperature may be 80 to 150° C., preferably 90 to 140° C., more preferably 100 to 130° C. The heating time may be 10 to 60 min, preferably 15 to 55 min, more preferably 20 to 50 min.
[0090] Limiting the heating conditions to the above range can ensure that the epoxy resin is completely melted and fully wraps the alloy powder, which is conducive to the prepared magnetostrictive material having better magnetostrictive properties under lower magnetic field intensity and improving the magnetic field sensitivity of the magnetostrictive material.
[0091] In the present invention, heating can be achieved using any heating device known in the art, which will not be described in detail here. For example, it can be a hot air blower or a flame spray gun, preferably a hot air blower. Cooling can be achieved by any type of cooling method known in the art, which is not particularly limited here. For example, it can be natural cooling or air cooling.
[0092] <Magnetostrictive Materials>
[0093] The present invention also provides a magnetostrictive material prepared by the preparation method.
[0094] According to one embodiment of the present invention, the magnetostrictive coefficient of the magnetostrictive material at a magnetic field intensity of 200 Oe may be 15 ppm or more, preferably 18 ppm or more, and more preferably 19 ppm or more.
[0095] According to one embodiment of the present invention, the magnetostrictive coefficient of the magnetostrictive material at a magnetic field intensity of 1000 Oe may be 200 ppm or more, preferably 210 ppm or more, and more preferably 214 ppm or more.
[0096] <Purpose>
[0097] The present invention also provides use of the magnetostrictive material in guided wave detection of metal materials.
[0098] In the present invention, the metal material can be any type of steel pipe or plate known in the art, which will not be described in detail herein. For example, it can be at least one of a stainless steel pipe or plate, a carbon steel pipe or plate, or other alloy steel pipes or plates.
[0099] <Guided Wave Testing Method for Metal Materials>
[0100] The present invention also provides a guided wave detection method for metal materials, comprising the following steps:
[0101] 1) mixing ball-milled powder or spherical powder of TbDyFe alloy with epoxy resin in a weight ratio of 1:0.2-1 to obtain a mixed powder;
[0102] 2) Using the metal material to be tested as the base of the mold, covering the upper surface of the metal material to be tested with the mixed powder, assembling the mold, and compacting the mixed powder in the mold. Then, the mixed powder is magnetically oriented at a magnetic field strength of 350 to 4000 Oe to obtain an oriented mixed powder and metal material assembly;
[0103] 3) Pressing the oriented mixed material and the metal material assembly at 50-400 MPa to obtain a pressed sheet and the metal material assembly;
[0104] 4) heating the pressed sheet and the metal material assembly at 80-150° C., cooling, and demolding to obtain a magnetostrictive material and metal material assembly;
[0105] 5) Place the combination of magnetostrictive material and metal material under a magnetic field and perform guided wave detection on the metal material to be tested.
[0106] According to one embodiment of the present invention, the metal material to be inspected may be a tube or a plate, preferably a tube. The outer diameter of the tube may be 50 to 90 mm, preferably 55 to 85 mm, and more preferably 60 to 80 mm. The thickness of the tube may be 1 to 5 mm, preferably 1 to 4 mm, and more preferably 2 to 4 mm.
[0107] <Test method>
[0108] Magnetostriction coefficient determination: The standard resistance strain gauge method is used in accordance with GB / T19396-2025, and the strain gauge is parallel to the magnetic field orientation direction.
[0109] Guided wave signal measurement: The MSGW guided wave instrument produced by Hangzhou Zheda Jingyi Company was used for detection.
[0110] <Ingredients>
[0111] Unless otherwise specified, the raw materials in the following examples are all commercially available products.
[0112] Epoxy resin E20 is bisphenol A epoxy resin purchased from Chuzhou Huisheng Electronic Materials Co., Ltd.
[0113] The stainless steel pipe to be tested is 304 stainless steel, provided by Humei Machinery Processing Factory in Baotou Rare Earth High-tech Zone, with specifications of: outer diameter 75mm, thickness 2mm, and length 150cm.
[0114] Preparation Example 1
[0115] Using Tb 0.27 Dy 0.73 Fe 1.92 The steps for preparing ball-milled powder of TbDyFe alloy are as follows:
[0116] Tb 0.27 Dy 0.73 Fe 1.92 The alloy was crushed into alloy blocks with a particle size of 5 mm. The alloy blocks were placed in a disc mill, and 2 mL of petroleum ether was added per gram of alloy block, followed by disc milling at a speed of 1200 rpm for 5 seconds to obtain disc milled powder.
[0117] The disc-milled powder was placed in a ball mill, and agate balls were added at a ball-to-material weight ratio of 10:7. Then, 8 mL of petroleum ether was added per g of disc-milled powder, and ball-milled for 30 min to obtain coarse ball-milled powder.
[0118] The coarse ball-milled powder is sieved to screen out powder of 75 to 125 μm to obtain ball-milled powder of TbDyFe alloy.
[0119] Preparation Example 2
[0120] Using Tb 0.27 Dy 0.73 Fe 1.93 The steps for preparing ball-milled powder of TbDyFe alloy are as follows:
[0121] Tb 0.27 Dy 0.73 Fe 1.92 The alloy was crushed into alloy blocks with a particle size of 5 mm. The alloy blocks were placed in a disc mill, and petroleum ether was added in an amount of 2 mL per gram of alloy block. Then, the alloy blocks were disc milled at a speed of 1200 rpm for 5 seconds to obtain disc milled powder.
[0122] The disc-milled powder was placed in a ball mill, and agate balls were added at a ball-to-material weight ratio of 5:3. Then, 8 mL of petroleum ether was added per g of disc-milled powder, and ball-milled for 30 min to obtain coarse ball-milled powder.
[0123] The coarse ball-milled powder is sieved to screen out powder of 75 to 125 μm to obtain ball-milled powder of TbDyFe alloy.
[0124] Comparative Preparation Example 1
[0125] Use Fe 83 Ga 17 The spherical powder of FeGa alloy is prepared by the following steps:
[0126] First, Fe 83 Ga 17 The oxide scale on the alloy surface is removed, and then Fe 83 Ga 17 The alloy surface is polished clean. 83 Ga 17 The alloy was placed in a vacuum melting furnace and smelted at 1700°C for 5 minutes to fully melt the alloy and obtain a uniform alloy liquid.
[0127] Under the conditions of argon gas and an atomizing pressure of 3.7 MPa, the alloy liquid was impacted into spherical powder to obtain coarse spherical powder.
[0128] The coarse spherical powder is sieved to separate powder of 50 to 125 μm to obtain spherical powder of FeGa alloy.
[0129] Comparative Preparation Example 2
[0130] Use Fe81 Ga 19 Tb 0.2 The spherical powder of FeGaTb alloy is prepared by the following steps:
[0131] First, Fe 81 Ga 19 Tb 0.2 The oxide scale on the alloy surface is removed, and then Fe 81 Ga 19 Tb 0.2 The alloy surface is polished clean. 81 Ga 19 Tb 0.2 The alloy is placed in a vacuum melting furnace and smelted at 1700°C for 5 minutes to fully dissolve the alloy and obtain a uniform alloy liquid.
[0132] Under the conditions of argon gas and an atomizing pressure of 3.7 MPa, the alloy liquid was impacted into spherical powder to obtain coarse spherical powder.
[0133] The coarse spherical powder is sieved to separate powder of 30 to 50 μm, thereby obtaining spherical powder of FeGaTb alloy.
[0134] Example 1
[0135] The ball-milled powder of the TbDyFe alloy obtained in Preparation Example 1 was fully mixed with epoxy resin E20 at a weight ratio of 5:4 to obtain a mixed powder.
[0136] The polished and cleaned stainless steel pipe to be tested serves as the mold base. The powder mixture is then applied to the top surface of the pipe. The mold is assembled and compacted into a 50mm-long, 10mm-wide, and 2mm-thick powder. The powder mixture is then oriented in a magnetic field at 500 Oe for 300 seconds to produce a composite of the oriented mixture and the metal material.
[0137] The oriented mixture and the metal material assembly are placed in a tablet press and pressurized at 100 MPa for 30 minutes to obtain a tablet and the metal material assembly.
[0138] The pressed sheet and the metal material assembly are heated at 120° C. for 30 minutes, and demolded after natural cooling to obtain a magnetostrictive material and metal material assembly.
[0139] Example 2
[0140] The ball-milled powder of the TbDyFe alloy obtained in Preparation Example 2 was fully mixed with epoxy resin E20 at a weight ratio of 10:7 to obtain a mixed powder.
[0141] The polished and cleaned stainless steel pipe to be tested serves as the mold base. The powder mixture is then applied to the top surface of the pipe. The mold is assembled and compacted into a 50mm-long, 10mm-wide, and 2mm-thick powder. The powder mixture is then oriented in a magnetic field at 3000 Oe for 300 seconds, resulting in a composite of the oriented mixture and the metal material.
[0142] The oriented mixture and the metal material assembly are placed in a tablet press and pressurized at 300 MPa for 30 minutes to obtain a tablet and the metal material assembly.
[0143] The pressed sheet and the metal material assembly are heated at 120° C. for 30 minutes, and demolded after natural cooling to obtain a magnetostrictive material and metal material assembly.
[0144] Comparative Example 1
[0145] The spherical powder of the FeGa alloy prepared in Comparative Preparation Example 1 was fully mixed with epoxy resin E20 at a weight ratio of 5:4 to obtain a mixed powder.
[0146] The polished and cleaned stainless steel pipe to be tested serves as the mold base. The mixed powder is then applied to the top surface of the pipe. The mold is assembled and compacted into a 50mm-long, 10mm-wide, and 2mm-thick powder. The mixed powder is then oriented in a magnetic field at 1000 Oe for 300 seconds to produce a composite of the oriented mixture and the metal material.
[0147] The oriented mixture and the metal material assembly are placed in a tablet press and pressurized at 100 MPa for 30 minutes to obtain a tablet and the metal material assembly.
[0148] The pressed sheet and the metal material assembly are heated at 120° C. for 30 minutes, and demolded after natural cooling to obtain a magnetostrictive material and metal material assembly.
[0149] Comparative Example 2
[0150] The spherical powder of the FeGaTb alloy prepared in Comparative Preparation Example 2 was fully mixed with epoxy resin E20 at a weight ratio of 10:7 to obtain a mixed powder.
[0151] The polished and cleaned stainless steel pipe to be tested serves as the mold base. The powder mixture is then applied to the top surface of the pipe. The mold is assembled and compacted into a 50mm-long, 10mm-wide, and 2mm-thick powder. The powder mixture is then oriented in a magnetic field at 3000 Oe for 300 seconds, resulting in a composite of the oriented mixture and the metal material.
[0152] The oriented mixture and the metal material assembly are placed in a tablet press and pressurized at 300 MPa for 30 minutes to obtain a tablet and the metal material assembly.
[0153] The pressed sheet and the metal material assembly are heated at 120° C. for 30 minutes, and demolded after natural cooling to obtain a magnetostrictive material and metal material assembly.
[0154] Experimental Example 1
[0155] The magnetostrictive materials and metal material assemblies prepared in Examples 1 and 2 and Comparative Examples 1 and 2 were placed in a magnetic field, and the magnetic field strength was gradually increased from 0 Oe to more than 1000 Oe. The magnetostrictive coefficients of the magnetostrictive materials under different magnetic field strengths were measured. The results are as follows: Figures 1 to 4 As shown in Table 1 below.
[0156] Table 1 Magnetostriction coefficients of magnetostrictive materials
[0157]
[0158] Depend on Figures 1 to 4 As shown in Table 1, the magnetostrictive performance of the magnetostrictive material of the present invention is significantly better than that of the comparative example. The magnetostrictive material prepared by the present invention also has good magnetostrictive performance under lower magnetic field intensity and high magnetic field sensitivity.
[0159] Application Experiment Example 1
[0160] The magnetostrictive material and metal material combination prepared in Example 2 was subjected to guided wave testing: two strong magnetizers were used, 10 cm apart, to apply a magnetic field with a magnetic field strength of 500 Oe to the magnetostrictive coating material using the north and south poles, respectively. A probe with a center frequency of 128 kHz was used for frequency sweeping. The results are shown in FIG. Figure 5 and 6 As shown. Figure 5 and 6 It can be seen that the waveguide instrument has a gain of 55dB at a test frequency of 43kHz, can receive obvious secondary waves and cubic waves, and the test signal is obvious, indicating that the magnetostrictive material of the present application can be effectively used in the guided wave detection of metal materials.
[0161] The present invention is not limited to the above-mentioned embodiments. Any modification, improvement, or substitution that can be conceived by those skilled in the art without departing from the essential content of the present invention shall fall within the scope of the present invention.
Claims
1. A method for preparing a magnetostrictive material, characterized in that: The following steps are involved: 1) mixing ball-milled powder or spherical powder of TbDyFe alloy with epoxy resin in a weight ratio of 1:0.2-1 to obtain a mixed powder; 2) placing the mixed powder obtained in step 1) in a mold and compacting it, and then orienting the mixed powder in a magnetic field at a magnetic field strength of 350 to 4000 Oe to obtain an oriented mixed material; 3) Pressing the oriented mixture obtained in step 2) at 50 to 400 MPa to obtain a pressed sheet; 4) heating the pressed sheet obtained in step 3) at 80-150° C., cooling, and demolding to obtain a magnetostrictive material.
2. The preparation method according to claim 1, characterized in that The chemical composition of the TbDyFe alloy is Tb a Dy b Fe c , a, b, c represent the number of atoms, a=0.1~0.5, b=0.5~1, c=1~3.
3. The preparation method according to claim 1, characterized in that The method for preparing the ball-milled powder of the TbDyFe alloy comprises the following steps: a) crushing the TbDyFe alloy to obtain an alloy block; grinding the alloy block for 2 to 10 seconds to obtain a grinding powder; b) ball milling the disc milled powder for 10 to 90 minutes at a ball-to-material weight ratio of 1:0.2 to 0.9 to obtain a coarse ball milled powder; c) sieving the coarse ball-milled powder to separate powder with a particle size of 65 to 150 μm to obtain ball-milled powder of TbDyFe alloy.
4. The preparation method according to claim 1, characterized in that The method for preparing the spherical powder of the TbDyFe alloy comprises the following steps: A) melting the TbDyFe alloy at 1500-1800°C to obtain a molten alloy; B) Under the conditions of protective gas and atomizing pressure of 2-5 MPa, impacting the alloy liquid into spherical powder to obtain coarse spherical powder; C) The coarse spherical powder is sieved to separate powder with a particle size of 65 to 150 μm, thereby obtaining spherical powder of TbDyFe alloy.
5. The preparation method according to claim 1, characterized in that In step 2), the magnetic field orientation time is 200 to 500 seconds.
6. The preparation method according to claim 1, characterized in that In step 3), the pressurization time is 10 to 60 minutes.
7. The preparation method according to claim 1, characterized in that In step 4), the heating time is 10 to 60 minutes.
8. A magnetostrictive material obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The magnetostrictive coefficient of the magnetostrictive material is greater than 15 ppm at a magnetic field strength of 200 Oe, and greater than 200 ppm at a magnetic field strength of 1000 Oe.
9. Use of the magnetostrictive material according to claim 8 in guided wave detection of metal materials.
10. A guided wave detection method for metal materials, characterized in that: The following steps are involved: 1) mixing ball-milled powder or spherical powder of TbDyFe alloy with epoxy resin in a weight ratio of 1:0.2-1 to obtain a mixed powder; 2) Using the metal material to be tested as the base of the mold, covering the upper surface of the metal material to be tested with the mixed powder, assembling the mold, and compacting the mixed powder in the mold. Then, the mixed powder is magnetically oriented at a magnetic field strength of 350 to 4000 Oe to obtain an oriented mixed powder and metal material assembly; 3) Pressing the oriented mixed material and the metal material assembly at 50-400 MPa to obtain a pressed sheet and the metal material assembly; 4) heating the pressed sheet and the metal material assembly at 80-150° C., cooling, and demolding to obtain a magnetostrictive material and metal material assembly; 5) Place the combination of magnetostrictive material and metal material under a magnetic field and perform guided wave detection on the metal material to be tested.
Citation Information
Patent Citations
Adhesive giant magnetostrictive material with laminated structure height (111) orientation and preparation method thereof
CN102569638A
Preparation method of binding rare-earth iron giant magnetostrictive material
CN102766792A
Magnetostrictive composite material for guided wave testing, as well as preparation method and application thereof
CN111850387A